Mobile IP-DECT internetworking architecture supporting IMT-2000 applications. - Gyasi-Agyei, A.
Realistic realization and mass acceptance of mobile data services require networking architectures offering acceptable quality of service and attractive tariffs. A novel strategy for this goal is maximum integration of popular data networking standards and their infrastructure into wireless networks. This article discusses a Mobile IP-based network architecture to provide IP services in DECT to support IMT-2000 applications. DECT offers micromobility within multicell subnets, while Mobile IP supports macromobility between multicell subnets. Incorporating Mobile IP into the DECT handoff mechanism in this way extends DECT micromobility with IP macromobility. Also, utilizing fast, seamless DECT handoff management reduces Mobile IP handoff delay to circumvent TCP throughput degradation during handoff and reduce frequency of Mobile IP signaling over the ether to conserve spectral efficiency. This feature seamlessly unifies DECT with the global Internet. Seamless integration of DECT with the Internet is crucial due to the continuing phenomenal popularity of the Internet and wireless communications, and ubiquity of DECT systems. To achieve the above DECT/IP interworking efficiently, the architecture introduces a network entity called a DECT service switching point, which is an extended DECT central control fixed part. DECT network-level services are mapped onto those of the IETF integrated services architecture to maintain QoS provided by DECT in the backbone Internet. Mobile Resource Reservation Protocol, an extended RSVP tailored to mobile networking, is adopted to provide the needed signaling in IntServ. The proposed architecture preserves traditional non-IP based services such as PSTN voice
Keywords: 3G mobile communication; DECT micromobility; DECT/IP interworking; IETF integrated services architecture; IMT-2000 applications; IP services; IP-DECT.; IntServ; Internet; Mobile IP signaling; Mobile IP-DECT internetworking architecture; Mobile Resource Reservation Protocol; PSTN voice; QoS; TCP; Data networking standards; Handoff delay reduction; Handoff management; Handoff mechanism; Mobile data services; Mobile multimedia services; Multicell subnets; Network entity; Network-level services; NonIP based services; Quality of service; Service switching point; Tariffs; Wireless networks